Manajemen Keuangan Sebagai Jantung Perusahaan Dalam Meningkatkan Daya Saing - Yuli Angraini (Institut Nalanda, 2026)
Financial management plays a crucial role in the sustainability and development of a company. In increasingly competitive business environments, companies are required to have the right financial management strategies to increase their competitiveness. This article aims to analyze the role of financial management as the core or